Antiretroviral Medication Adherence and Amplified HIV Transmission Risk Among Sexually Active HIV-Infected Individuals in Three Diverse International Settings - Magidson J. (2017)
© 2015, Springer Science+Business Media New York. Successful biomedical prevention/treatment-as-prevention (TasP) requires identifying individuals at greatest risk for transmitting HIV, including those with antiretroviral therapy (ART) nonadherence and/or ‘amplified HIV transmission risk,’ defined as condomless sex with HIV-uninfected/unknown-status partners when infectious (i.e., with detectable viremia or STI diagnosis according to Swiss criteria for infectiousness). This study recruited sexually-active, HIV-infected patients in Brazil, Thailand, and Zambia to examine correlates of ART nonadherence and ‘amplified HIV transmission risk’. Lower alcohol use (OR = .71, p  <  .01) and higher health-related quality of life (OR = 1.10, p  <  .01) were associated with greater odds of ART adherence over and above region. Of those with viral load data available (in Brazil and Thailand only), 40 % met Swiss criteria for infectiousness, and 29 % had ‘amplified HIV transmission risk.’ MSM had almost three-fold (OR = 2.89, p  <  .001) increased odds of ‘amplified HIV transmission risk’ (vs. heterosexual men) over and above region. TasP efforts should consider psychosocial and contextual needs, particularly among MSM with detectable viremia.